Molecular Profiling for Blast Resistance Genes Pita2 and Pi2/Pi9 in Some Rice (Oryza sativa L.) Accessions and Selected Crosses - Walaa M. Essa; Nesreen N. Bassuony; Abed El-aziz Tahoon; Abeer M. Mosalam; József Zsembeli (Agriculture)
Identifying major blast resistance genes in Oryza sativa L. genotypes is key to enhancing and maintaining the resistance. Observing rice varieties with durable resistance to blast has become a potential target in rice breeding programs. In this study, an evaluation was conducted during 2020 and 2021 on ten Egyptian and introduced varieties. First, a field experiment was conducted in a randomized complete block design with three replications, and it was found that the Egyptian cultivar Sakha 101 had the highest crop grain yields (53.27 g). The Spanish varieties Hispagrán and Puebla were the earliest (110 and 108 days, respectively) as well as the highest in 1000-grain yield, giving them priority as donors for these traits; however, they had the lowest mean values in the number of panicles. Second, these cultivars were subjected to eighteen isolates from five strains of Pyricularia oryzae (IH, IC, ID, IE, and II). The Egyptian varieties Giza 177, Giza 179, Sakha 106, Giza 182, GZ1368-5-5-4, and GZ6296 were 100% resistant, while Hispagrán’s resistance was 16.6%, followed by Sakha 101 with 27.8%. To gain insight into the ten varieties, we used STS, SCAR, and CAPS markers to detect and mine alleles for major blast broad-spectrum resistance genes Pi2, Pi9, and Pita2. In the context of considering gene pyramiding as an effective strategy for achieving broad durable spectrum resistance to blast, molecular profiling was also conducted on eighteen F2 single plants obtained from the hybridization of Giza 177 (resistant) × Puebla (susceptible) varieties. Also, eighteen F2 single plants were obtained from Giza 177 × Hispagrán (highly susceptible) varieties. Conducting a molecular scan with STS dominant marker YL153/YL154 was performed on ten cultivars to detect the presence of the Pita2 gene, which conferred a unique band in Puebla. By doing a scan of the 18 second-generation plants derived from Giza 177 × Puebla, 11 individual plants of the 18 plants obtained a band, which was transferred from Puebla. F2 plants obtained from Giza 177 × Puebla amplified with CAPS marker RG64-431/RG64-432 had higher numbers of Pi2 alleles, while F2 plants of Giza 177 × Hispagrán cross-amplified with SCAR marker linked to Pi9 exceeded their parents more. Our results have revealed that molecular markers played an essential role in determining the direction of evolution for blast resistance traits.